Undivided Corporate Responsibility: Towards a Theory of Corporate Integrity - Maak, Thomas (Journal of business ethics, 2008)
In the years since Enron corporate social responsibility, or “CSR,” has become a ubiquitous phenomenon in both research and business practice. CSR is used as an umbrella term to describe much of what is done in terms of ethics-related activities in firms around the globe to such an extent that some consider it a “tortured concept” (Godfrey and Hatch 2007, Journal of Business Ethics 70, 87–98). Addressing this skepticism, I argue in this article that the focus on CSR is indeed problematic for three main reasons: (1) the term carries a lot of historical baggage – baggage that is not necessarily conducive to the clarity of the concept; (2) it is the object of increasing ethical instrumentalism; and (3) given the multiple ethical challenges that corporations face, and given the fact that the “social” responsibilities of business are but one set of corporate responsibilities, a suitable term would have to be more inclusive and integrative. I therefore suggests moving instead toward a sound definition of corporate integrity and aim in this article to develop a working definition by fleshing out “7 Cs” of integrity: commitment, conduct, content, context, consistency, coherence, and continuity. I then discuss how these 7 Cs impact our understanding of CSR or, more broadly, corporate responsibility in general.